Speech Acts of Protest Expressed by Followers of the World Health Organization Instagram Account - Tri Utami, Sanita; Yanti, Yusrita (KnE Social Sciences, 2022)
In response to the COVID-19 pandemic that has hit the world, the World Health Organization (WHO), as a frontline organization, provides education and information about COVID-19 regularly. The WHO uses Instagram as a social media platform to share information about COVID-19. This Instagram account garners many responses from its followers who express their comments in different ways. The pros and cons of COVID-19 policies have caused protests from people around the world. In this study, the researchers observed the speech acts of protest expressed by the followers of the WHO Instagram account. The data for this study were taken from the comments of WHO followers directed to two posts related to COVID-19 that received many responses. This was qualitative research and the theoretical concept used referred to the theory of speech acts, co-text, contexts, and function. The results showed that the function of the speech acts of protest was to express a sense of blaspheming, slandering, or judging. The results of this study are useful for scholars who observe speech acts, especially those that have functions to express emotions using various strategies. Keywords: expressive speech act of protesting, function, context, WHO Instagram